Impact of Social Isolation on Anxiety and Depression Post COVID-19 Pandemic: Challenges and Solutions - Al Hussaini, Muzamil Hussain; Kausar, Shumaila; Ul Huda Shah, Muhammad Tabarak; Munawar, Nousheen (The Indonesian Institute of Science and Technology Research, 2024)
The COVID-19 pandemic has markedly impacted mental health worldwide, with social isolation being a significant factor contributing to increased anxiety and depression. This research explores the psychological effects of prolonged social isolation during and after the pandemic. The study aims to assess the prevalence of anxiety and depression, identify associated risk factors, and propose effective interventions. The hypothesis posits that increased social isolation correlates with heightened levels of anxiety and depression. The population for this study includes adults aged 18-65 from both urban and rural areas. 500 participants were selected using stratified random sampling to ensure a diverse demographic representation. This cross-sectional study adopts a mixed-methods approach, combining quantitative surveys and qualitative interviews. Data collection tools include the Generalized Anxiety Disorder (GAD-7) scale and the Patient Health Questionnaire (PHQ-9), along with semi-structured interview guides. Quantitative data were analyzed using statistical techniques such as regression analysis, while qualitative data were undergone thematic analysis. The results offer insights into the mental health challenges posed by social isolation and suggest evidence-based solutions to mitigate these effects.